Technology Success and Failure in Winner-Take-All Markets: The Impact of Learning Orientation, Timing, and Network Externalities - Schilling, Melissa A. (Academy of Management Journal, 2002)
In industries characterized by network externalities, a single technology standard often rises to dominance, locking out competing technologies. This research demonstrates that despite ?path dependency,? it is possible to model the technology selection process and predict likely outcomes. This work extends previous work in network externalities by demonstrating that in addition to its ?installed base? and the availability of complementary goods, a firm's learning orientation and timing of entry also play significant roles in its success.